2024
DOI: 10.1002/anie.202318665
|View full text |Cite
|
Sign up to set email alerts
|

Development of Better Aptamers: Structured Library Approaches, Selection Methods, and Chemical Modifications

Alex Brown,
Jake Brill,
Ryan Amini
et al.

Abstract: Systematic evolution of ligands by exponential enrichment (SELEX) has been used to discover thousands of aptamers since its development in 1990. Aptamers are short single‐stranded oligonucleotides capable of binding to targets with high specificity and selectivity through structural recognition. While aptamers offer advantages over other molecular recognition elements in their ease of production, smaller size, extended shelf‐life, and lower immunogenicity, they have yet to show significant success in real‐worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 209 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, we discuss the principal methodologies and techniques used to enhance the overall efficiency and functionality of aptamers for improved target detection. Recently, two reviews have described aptamer identification, the transducer technologies used in aptasensors and nanomaterials for aptasensors [17][18][19][20][21][22][23]. Differing from these reports, the current review aims to demonstrate the present circumstances and the prospects of various aptasensors for the detection of pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we discuss the principal methodologies and techniques used to enhance the overall efficiency and functionality of aptamers for improved target detection. Recently, two reviews have described aptamer identification, the transducer technologies used in aptasensors and nanomaterials for aptasensors [17][18][19][20][21][22][23]. Differing from these reports, the current review aims to demonstrate the present circumstances and the prospects of various aptasensors for the detection of pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, many methods have been reported for the selective detection of antibody levels. In addition to liquid chromatography–mass spectrometry (LC–MS)-based methods that do not require the use of an affinity ligand, a variety of methods utilizing antibodies, peptide mimotopes, and aptamers, , as the affinity ligands have been reported, such as the surface plasmon resonance (SPR), chemiluminescent, photoelectrochemical (PEC), bioluminescent, fluorescent, , quartz crystal microbalance (QCM), and electrochemical methods. Among these methods, the electrochemical aptamer-based (E-AB) detection of antibody pharmaceuticals has received increasing attention, largely due to the good portability, low sample consumption and detection cost, and uncomplicated instrumentation. , On the basis of the binding-induced conformational change of the ferrocene (Fc)-modified DNA aptamer, for example, Nagata et al reported an E-AB method for the one-step detection of bevacizumab, with a detection limit of 9.1 nM . This method is easy to operate, low-cost, and highly selective; however, the “signal-off” detection can result in false-positive responses while the detection sensitivity remains to be further improved.…”
mentioning
confidence: 99%
“…Many nucleic acid aptamers, characterized by their propensity to adopt specific structural conformations, also fold into noncanonical structures, thus forming unique threedimensional architectures capable of specifically recognizing their targets at the molecular level [12,13]. Moreover, the nanoscale geometry and dynamic properties of noncanonical nucleic acid structures, along with their inherent biocompatibility, make them promising candidates for the development of functional nanodevices [14,15].…”
mentioning
confidence: 99%